Three-dimensional electromagnetics proceedings of the second international symposium - Zhdanov, Mikhail Semenovich; Wannamaker, P. E. (Elsevier, 2002)
"3-D modeling and inversion is a reality, and not an illusion." This is the clear conclusion of the Second International Symposium on Three-Dimensional Electromagnetics held at the University of Utah in 1999. Containing papers submitted by 36 authors, this volume, by the sheer number of works, their diversity, and the truly international character of the efforts attests to the vigor with which the problems of the field are pursued today. The papers in this book are grouped in three parts: 3-D EM modeling; 3-D EM inversion; and 3-D EM in practice. They cover a wide range of topics in forward modeling and inversion based on new fast approximate approaches and new efficient solutions by integral equation, finite difference and finite elements techniques. If the 1980s were the decade of rapid development in 3D seismics, the 1990s became the decade of growing interest of practical geophysicists in 3D EM modeling and inversion methods. The contributions contained in this volume represent a snapshot of today's state-of-the-art in three-dimensional electromagnetics.
Keywords: Magnetic prospecting -- Congresses.; elektronické knihy; electronic books